PERAN GEREJA DALAM PENGEMBANGAN PROGRAM KEWIRAUSAHAAN DI ERA DIGITAL - Purnama Pasande; Ezra Tari (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2019)
In the digital era, the Church's role in developing entrepreneurial programs faces new challenges through the application. Many entrepreneurship development models include a church located in a mall. There are also cooperatives within the Church selling snacks, many small and medium businesses, food stalls, and others. The Church must be creative in developing entrepreneurship, especially in this digital era. The research method used in this article is a qualitative research method with descriptive analysis. The research found entrepreneurial diversity that showed numerous dissimilar things to one another. Therefore, the Church must be active in fulfilling spiritual and physical needs.